Analisis Perbandingan Metode Analytic Hierarchy Processs (AHP) Dan Fuzzy AHP Untuk Evaluasi Overall Equipment Effectiveness (OEE) Mesin Screw Press Di PTPN V Sei Pagar - Riyandi Al Isral.Z; Anita Susilawati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
This paper aims to compare between method of AHP (Analytical Hierarchy Process) and fuzzy AHP to evaluate the OEE values on screw press machine in PTPN V Sei. Pagar. The analyzing of criteria and sub-criteria in the hierarchy model to rank alternative selection actions to minimize the screw press machines losses was done in this paper. Two critical losses occurring in the screw press machine were setup and adjustment losses, and equipment failure losses. The result showed for the AHP method, the most influential criteria for setup and adjustment losses were workers with a value of 0.567 and the highest alternative value of action for periodic checking. The equipment failure losses were obtained the most influential criteria of the machine with a value of 0.444 and the best alternative selection action that was the human resources development. For Fuzzy AHP method of setup and adjustment loss, the most influential criteria was workers with value of 0.555, and best alternative action was periodic checking. Equipment failure loss was obtained the most influential criteria for machines with a value of 0.444 and the best alternative selection action was the human resource development. From the comparison of both methods, it can be concluded that the AHP method was more simple in terms of data processing. However, the fuzzy AHP method was revealed more accurate values due to not containing subjective judgment in terms of selection action to improve the effectiveness of the screw press machine.Keywords :OEE, AHP, Fuzzy AHP, Screw Press